[PP.13.02] DETERMINANTS OF CENTRAL HYPERTENSION IN ADOLESCENTS WITH ELEVATED BLOOD PRESSURE – PRELIMINARY RESULTS. (September 2017) - Obrycki, L.; Derezinski, T.; Sarnecki, J.; Kulaga, Z.; Litwin, M.
Abstract : Objective: Spurious hypertension (SH) is a phenomenon of elevated blood pressure assessed on the brachial artery with normal values of blood pressure in the aorta. It is assumed that the SH is not connected with target organ damage (TOD) and cardiovascular risk and should not be treated. The aim of the study was to compare the clinical and hemodynamic intermediate phenotypes in adolescents with arterial hypertension (AH) and SH and assess predictors of SH. Design and method: Of 240 students in whom brachial blood pressure were measured, 64 adolescents (27 girls; 14.6 ± 0.7 years), in whom AH was diagnosed based on elevated blood pressured found on 3 independent occasions were included to the study. Left ventricular mass index (LVMi), carotid intima-media thickness (cIMT), pulse wave velocity (PWV), central systolic (cSBP) and pulse pressure (cPP) was measured in all hypertensive children. PWV, cSBP and cPP were assessed using oscillometric device (Vicorder®). Results: AH described as elevated both peripheral and cSBP was confirmed in 32 subjects (50%) [23 boys (62.2%) and 9 girls (33.3%); p = 0.04]. Patients with AH had significantly greater waist circumference (WC), body mass index (BMI), peripheral pulse pressure and cPP, cardiac index and stroke volume of the left ventricle compared with SH children (for all comparisons p < 0.05). Left ventricular hypertrophy (LVH) was found in 15 subjects (9 (28%) with AH and 6 (18.7%) with SH. Elevated BMI, visceral obesity and higher cPP, correlated with cSBP. However, multivariate logistic regression analysis showed that the only predictor of elevated cSBP was the male sex. Conclusions: Of all adolescents diagnosed as AH, SH was found in 50%. Visceral obesity, overweight and symptoms of the hyperkinetic circulation were associated with the diagnosis of AH, but the only predictor of AH was a male sex. However, finding of LVH in 18.7% of subjects with SH needs further studies.